Performance of Geogrid Reinforced Sand Layer overlaying Encased Stone Peirs for Founding on Soft Clay Deposits - Eltohamy, Ahmed Mohamed (International Journal of Scientific Research in Civil Engineering, 2019)
Reinforcing deep soft clay layers with rammed aggregate piers is one of the most effective and economical techniques. However, the un-replaced soft clay area weakens the reinforced system and results in a relatively large amount of differential settlement. The present numerical investigation aims at examining the usefulness of reinforcing the fill layer overlaying the piers with Geogrid sheets. The soil –pier - Geogrid interaction is investigated by considering the following factors: Geogrid tensile stiffness, pier spacing, pier–soil stiffness ratio and preloading deformation of Geogrid reinforcement layer. Geogrid reinforcement of fill layer above piers significantly improved the carrying capacity of the system and reduced maximum and differential settlement, soil arching and stress concentration. Pier-soil stiffness ratio of relatively high range has little effect on the performance of the system. When the footing is placed over the pier Geogrid reinforcement does not have an influence on reinforced system. Forming a dish shaped Geogrid sheet between piers effectively improved system performance.